ALGORITHMS FOR CALCULATION NETWORK SCEDULES SET BY FAMILY OF NODAL SUBSETS - Литвиненко, О.; Мельник, С.; Ментю, М. (Science-based technologies, 2010)
Advantages of the list form of the description of the oriented graph in comparison with the matrix form are proved. Algorithms of calculation of the network schedules set by family of nodal subsets are resulted.